2006
DOI: 10.1111/j.1439-0523.2006.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of resistance to Fusarium head blight in wheat using a ‘Frontana’‐derived population

Abstract: Fusarium head blight (FHB or head scab) has become a major limiting factor for sustainable wheat (Triticum aestivum L.) production around the world. For quantitative trait loci (QTL) analysis of resistance to FHB, F 3 plants and F 3 : 5 lines, derived from a ÔFrontanaÕ (moderately resistant)/ÔSeri82Õ (susceptible) cross, were spray-inoculated in 2001 and 2002, respectively. Artificial inoculations were carried out under field conditions. Of 273 SSR and AFLP markers, 250 could be mapped and they yielded 42 link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…This highlights the importance of appropriate testing for the detection of some FHB QTL that are, perhaps, only effective under particular conditions. We observed FHB QTL on 2B and 7A, in common with the reports of Steiner et al (2004) and Mardi et al (2006), respectively. Both previous studies found Frontana to carry alleles on 1B that were deleterious for FHB resistance compared to the other parent.…”
Section: Ph-j2000supporting
confidence: 73%
See 3 more Smart Citations
“…This highlights the importance of appropriate testing for the detection of some FHB QTL that are, perhaps, only effective under particular conditions. We observed FHB QTL on 2B and 7A, in common with the reports of Steiner et al (2004) and Mardi et al (2006), respectively. Both previous studies found Frontana to carry alleles on 1B that were deleterious for FHB resistance compared to the other parent.…”
Section: Ph-j2000supporting
confidence: 73%
“…In addition, a QTL of small effect on 1BL was contributed by Remus, the susceptible parent. Subsequently, Mardi et al (2006) confirmed the QTL on 3A and detected an additional QTL on 7AS. They also detected a QTL on 1BL originating from Seri82, the susceptible parent of their mapping population.…”
Section: Ph-j2000supporting
confidence: 54%
See 2 more Smart Citations
“…SSR markers occur frequently in most eukaryote genomes and can be highly informative and reproducible (Gupta et al, 1996). The AFLP technique is laborious and time consuming but is also able to detect many polymorphisms with each primer combination (Mardi et al, 2005(Mardi et al, , 2006. Proteomic analysis showed to be a powerful approach to analyse crop proteomics (Salekdeh & Komatsu, 2007).…”
Section: Introductionmentioning
confidence: 99%